Analysis On The Performance Of Led And Laser Diode With Charge Coupled Device (CCD) Linear Sensor Measuring Diameter Of Object - Juliza Jamaludin; Rahim, RA; Rahim, HA; Rahiman, HF; Muji, SZM; Jumaah, MF; Fadzil, NSM; Ahmad, N; Sahlan, S; Ahmad, A; Yunus, Y; Abas, KH (Penerbit UTM Press, 2024)
Indexed by WOS